Behavior of shade-weathered and photo-oxidized crude oil with and without application of dispersant under breaking wave conditions - Ruixue Liu; Wen Ji; Cosan Daskiran; Fangda Cui; Charbel Abou-Khalil; Jianyun Li; Anirban Dhulia; Michel Boufadel; Subhamoy Gupta; Joseph Katz; Baiyu Zhang; Kenneth Lee (Marine Pollution Bulletin, 2026)

Effect of sprinkler-based water application in mitigating ammonia emissions from beef cattle feedyards - Myeongseong Lee; Brent W. Auvermann; K. Jack Bush; Greg B. Ferguson; Carolina B. Brandani; Kenneth D. Casey; Vinícius N. Gouvêa; Jason K. Smith; Luis O. Tedeschi; Jacek A. Koziel (Biosystems Engineering, 2026)

Functional analysis of stem-loop structures within the SARS-CoV-2 5′ untranslated region using a plasmid-based reporter system - Sylvia Yahumin; Ping Chin Lee; Caroline Sunggip; Kenneth Francis Rodrigues (Archives of Virology, 2026)

Oil spills in inland freshwaters: A review of recent incidents, mitigation practices, and ecological impacts in the United States - Joshua O. Olowoyo; Nan Zou; David Cooper; Kurt Hansen; Vince Palace; Kenneth Lee; Qin Xin; Amarjeet Bassi; Ying Zheng (Science of The Total Environment, 2026)

Artificial intelligence for marine oil spill management: Recent advances and future directions - Ziyu Wang; Yawen Huang; Guorui Zhang; Zhihan Wang; Zhi Chen; Catherine N. Mulligan; S. Samuel Li; Maria Elektorowicz; Biao Li; Kenneth Lee; Chunjiang An (Marine Environmental Research, 2026)

Modernization of the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) Program: Rationale and Overview of the THIS-WIC (Telehealth Intervention Strategies for WIC) Project - Catherine Wright; Pascasie Adedze; Alice Ammerman; Lauren Au; Alan Barnosky; Jonathan Blitstein; Karen Castellanos-Brown; Sheryl Cates; Madhur Chandra; Kenneth Kwan Ho Chui; Katharine Clarke; Christina Economos; et al. (Journal of Nutrition Education and Behavior, 2026)

Retinoic acids can hinder molting and development of the marine copepod Tigriopus japonicus in the coastal environment - Guang-Jie Zhou; Racliffe Weng Seng Lai; Yi Yang; Min-Sub Kim; Young Hwan Lee; Jae-Seong Lee; Kenneth Mei Yee Leung (Journal of Hazardous Materials, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Histone deacetylases and cell-cycle regulators orchestrate cell-identity transitions during Arabidopsis root regeneration - Ramin Rahni; Laura R. Lee; Graeme Vissers; Indie Suresh; Brandon M. Gorodokin; Pui-Leng Ip; Bruno Guillotin; Kenneth D. Birnbaum (Molecular Plant, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Identification of Genetic Variation Associated With Heat Tolerance in Cowpea ( Vigna unguiculata L. Walp.) - Roland Akakpo; Elaine J. Lee; Jacob B. Pacheco; Esteban F. Rios; Michael B. Kantar; Ousmane Boukar; Kevin M. Volz; Habib Akinmade; Luis Getino; Kenneth J. Boote; María Muñoz‐Amatriaín; Peter L. Morrell (Molecular Ecology, 2026)
Heat tolerance is an important trait in cowpea, a crop that is the primary protein source for a large portion of the human population in sub‐Saharan Africa. Cultivated, landrace, semi‐wild, and wild cowpea grow across the region in diverse climatic conditions. This study used environmental association (envGWAS) and allele‐frequency outlier approaches across a panel of 580 gene bank accessions to identify genomic regions associated with adaptation to heat and limited precipitation. Allele frequency outliers are detected independent of potential selective factors driving differentiation; we used a ranking‐based approach to identify the climate variables most associated with variants among outliers. Precipitation‐related variables dominated the signals we identified for envGWAS and allele frequency outliers. We identified variants on all 11 chromosomes that are putatively associated with cowpea adaptation to higher‐temperature environments. The overlap between variants associated with low precipitation and high temperature suggests that these traits may be inextricably linked in cowpea. The Sahel region is the source of many accessions with derived variants associated with high temperatures, suggesting that accessions from this region could contribute heat tolerance alleles for cowpea improvement.

Wood oil biodegradation in the marine environment: Behavior, mechanism, and impact - Hongyi Li; Bing Chen; Yiqi Cao; Min Yang; James Brydie; Kenneth Lee; Baiyu Zhang (Water Research, 2026)

Acoustic Monitoring of Two Seagrass Meadows Reveals Differences in Oxygen Ebullition and Biomass - Megan S. Ballard; Kyle A. Capistrant-Fossa; Kevin M. Lee; Andrew R. McNeese; Colby W. Cushing; Robert T. Taylor; Thomas S. Jerome; Kenneth H. Dunton; Preston S. Wilson (Estuaries and Coasts, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Oil on the beach: A laboratory investigation into the influence of temperature on oil penetration into shoreline sediments - Lee Britton; Ed Owens; Tom King; Kenneth Lee; Bing Chen (Marine Pollution Bulletin, 2026)

Perspectives on Messaging Strategies to Increase Participation in Universal Free School Meal Programs: A Qualitative Study With Parents of Elementary School-Aged Children - Amanda B. Zeitlin; Alix Zuceth Durán Gómez; Cristina J.Y. Lee; Andrea Pedroza-Tobias; Christina A. Hecht; Anisha I. Patel; Kenneth Hecht; Anna H. Grummon (Journal of the Academy of Nutrition and Dietetics, 2026)

Prediction of microplastic transport in oil-contaminated waters - Min Yang; Bing Chen; Qiao Kang; Anran Wang; Runbo Yuan; Xiujuan Chen; Kenneth Lee; Baiyu Zhang (Marine Pollution Bulletin, 2026)

Host influence on survival and growth of two sandalwood species during early development - Duc Bui; David J. Bush; Kenneth J. Robson; D.J. Lee (Forest Ecology and Management, 2026)

PFAS retention and distribution in the vadose zone of three soil types impacted by biosolids application - Lynda Godwin Peter; Linda S. Lee; Chris Burbage; Kenneth Hoffman; April Richardson (Journal of Environmental Management, 2025)

Dual aging pathways of Cu-SSZ-13 SCR catalysts: Hydrothermal vs. sulfur-induced deactivation - Dhruba J. Deka; Tahrizi Andana; Rohil Daya; Feng Gao; Eric D. Walter; Jian Zhi Hu; Garam Lee; Mark Bowden; Yong Wang; Kenneth G. Rappe (Chemical Engineering Journal, 2025)

Emerging per- and polyfluoroalkyl substances (PFAS) cause intestinal toxicity in marine medaka (Oryzias melastigma) - Naiyu Xie; Qi Wang; Shicong Du; Yingyu Bao; Yetong Shao; Linjie Jin; Yutong Zhang; Meng Yan; Patrick K.H. Lee; Kenneth M.Y. Leung; Paul K.S. Lam; Yuefei Ruan (Aquatic Toxicology, 2025)

Nicotinamide riboside supplementation restores microglial health and improves cognition in aged male mice - Ramkumar Thiyagarajan; Rupadevi Muthaiah; Bhavana Sreevelu; Owen P. Treanor; Yonas Redae; Reem Berman; Anna L. Davis; Nanda Yellapu; Spencer R. Rosario; Lee D. Chaves; Kenneth L. Seldeen; Bruce R. Troen (GeroScience, 2025)
Cognitive impairment affects 1 in 6 individuals over 60, with over 75 million projected by 2030. Age-related changes in microglial function and declining nicotinamide adenine dinucleotide (NAD + ) levels may contribute to cognitive decline. Although nicotinamide riboside (NR) supplementation can restore NAD + levels in aged mice, its effects on microglial phenotype and cognition during normal aging remain unclear. We assessed cognitive function, neuroinflammation, and microglial gene expression in 6-month (Young) and 22-month (Aged) mice, along with aged mice supplemented with NR (Aged + NR; 400 mg/kg body weight) for 8 weeks. Aged mice exhibited impaired cognition and increased gene expression related to neuroinflammation. NR supplementation improved or prevented the decline in nest-building ability, Y-maze spontaneous alternation, and novel object recognition, which are reflective of instrumental activities of daily living, spatial working memory, and recognition memory. NR supplementation diminished microglial (IBA1) and astrocytic (GFAP) activation, resembling the young phenotype. Gene expression profiling revealed reduced microglial activation, inflammatory pathways, and chemokine production in Aged + NR mice, along with upregulation of genes associated with learning, memory, and gliogenesis. NR lowered transcriptional signatures from age-dependent (ADEM) and disease-associated (DAM) microglia and enhanced homeostatic state profiles. Metabolic pathway analysis of microglial transcripts indicated that NR suppressed age-induced increases in fatty acid metabolism. This was supported by immunostaining, which showed reduced lipoprotein lipase (LPL), a DAM marker, in the cortex and hippocampus. Overall, NR appeared to mitigate age-related cognitive decline by shifting microglial gene expression and metabolism toward a younger phenotype, suggesting potential therapeutic relevance for healthy brain aging.

Transformations of particulate organic matter from the surface to the abyssal plain in the North Pacific as inferred from compound-specific stable isotope and microbial community analyses - Lee C. Miller; Hilary G. Close; Kalina C. Grabb; Christine L. Huffard; Fuyan Li; David M. Karl; Kenneth L. Smith; Edward F. DeLong; Claudia R. Benitez-Nelson; Jeffrey C. Drazen; Brian N. Popp (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Protecting shorelines in Canadian Indigenous communities: Environmental challenges, policy interventions, and mitigation technologies - Rezvan Iravani; Mark Biagi; Sonia Laforest; Kenneth Lee; Lisa Isaacman; Zhi Chen; Chunjiang An (Marine Pollution Bulletin, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Impact of below-freezing air temperatures on the formation and stability of seawater-crude oil emulsion - Jianyun Li; Wen Ji; Roger C. Prince; Kenneth Lee; W. Scott Pegau; Michel Boufadel (Marine Pollution Bulletin, 2025)

Implications for cost-competitiveness of misalignment in hydrogen certification: a case study of exports from Australia to the EU - Lee V. White; Reza Fazeli; Fiona J. Beck; Kenneth G.H. Baldwin; Chengzhe Li (Energy Policy, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

GOOSM: A GIS-based offshore oil spill management tool for enhanced response and preparedness - Zhaoyang Yang; Zhi Chen; Kenneth Lee (Marine Pollution Bulletin, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Correction: Remote Ischemic Postconditioning vs. Physical Exercise After Stroke: an Alternative Rehabilitation Strategy? - Xiaokun Geng; Qingzhu Wang; Hangil Lee; Christian Huber; Melissa Wills; Kenneth Elkin; Fengwu Li; Xunming Ji; Yuchuan Ding (Molecular Neurobiology, 2025)

Well-being of park users in a tropical city may be more influenced by their nature connectedness and exposure than bird diversity - Angelia Sia; Malcolm C.K. Soh; Wee Meng Lee; Hock Jin Poon; Kenneth B.H. Er (Urban Forestry & Urban Greening, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Influence of saline water and heavy rain on the fate of chlorinated ethenes in groundwater characterized by compound-specific isotope and microbial data - Dugin Kaown; Kenneth C. Carroll; Jürgen Mahlknecht; Ye Ji Kim; Jun-Young Shin; Seong-Sun Lee; Kang-Kun Lee (Journal of Hazardous Materials, 2025)

Long-term field study of nitrate and ammonium remediation using a permeable reactive barrier at a livestock feeding operation - Michael Lawrinenko; Lee Rhea; Kenneth J. Forshay; Tony R. Lee; Mark White; Richard T. Wilkin (Journal of Environmental Management, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Prenatal exposure to heat and humidity and infant birth size in Ghana - Aalekhya Reddam; Mohammed Nuhu Mujtaba; Cascade Tuholske; Seyram Kaali; Kenneth Ayuurebobi Ae-Ngibise; Blair J. Wylie; Danielle N. Medgyesi; Ellen Boamah-Kaali; Andrea A. Baccarelli; Oscar Agyei; Steve N. Chillrud; Kwaku Poku Asante; et al. (Environmental Research, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Oil spills in coastal regions of the Arctic and Subarctic: Environmental impacts, response tactics, and preparedness - Huifang Bi; Zheng Wang; Rengyu Yue; Jiyao Sui; Catherine N. Mulligan; Kenneth Lee; Scott Pegau; Zhi Chen; Chunjiang An (Science of The Total Environment, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Automating urban soundscape enhancements with AI: In-situ assessment of quality and restorativeness in traffic-exposed residential areas - Bhan Lam; Zhen-Ting Ong; Kenneth Ooi; Wen-Hui Ong; Trevor Wong; Karn N. Watcharasupat; Vanessa Boey; Irene Lee; Joo Young Hong; Jian Kang; Kar Fye Alvin Lee; Georgios Christopoulos; et al. (Building and Environment, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Multiscale Finite Element Modeling of Left Ventricular Growth in Simulations of Valve Disease - Hossein Sharifi; Mohammad Mehri; Charles K. Mann; Kenneth S. Campbell; Lik Chuan Lee; Jonathan F. Wenk (Annals of Biomedical Engineering, 2024)

Southern Flounder: Major Milestones and Remaining Knowledge Gaps in Their Biology, Ecology, and Fishery Management - Stephen R. Midway; Frederick S. Scharf; Michael A. Dance; Nancy J. Brown-Peterson; Joseph C. Ballenger; Nicolette S. Beeken; Russell J. Borski; Tanya L. Darden; Kenneth A. Erickson; Troy M. Farmer; Ashley Fincannon; John Godwin; et al. (Reviews in Fisheries Science & Aquaculture, 2024)

Managing deepsea oil spills through a systematic modeling approach - Zhi Chen; Zhaoyang Yang; Kenneth Lee; Youyu Lu (Journal of Environmental Management, 2024)

A multi-criteria simulation-optimization coupling approach for effective emergency response in marine oil spill accidents - Xudong Ye; Baiyu Zhang; Kenneth Lee; Rune Storesund; Xing Song; Qiao Kang; Pu Li; Bing Chen (Journal of Hazardous Materials, 2024)

Effect of nanobubbles on the mobilization of microplastics in shorelines subject to seawater infiltration - Zheng Wang; Kenneth Lee; Qi Feng; Chunjiang An; Zhikun Chen (Environmental Pollution, 2024)

Piezocatalytic property of PVDF/Graphene self-assembling piezoelectric membrane for environmental remediation - Tsung-Han Huang; Franz Kenneth C. Espino; Xin-Yuan Tian; Januar Widakdo; Hannah Faye M. Austria; Owen Setiawan; Wei-Song Hung; Kristopher Ray S. Pamintuan; Rhoda B. Leron; Ching-Yuan Chang; Alvin R. Caparanga; Kueir-Rarn Lee; et al. (Chemical Engineering Journal, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Cruise observation of ambient volatile organic compounds over Hong Kong coastal water - Hao Sun; Dasa Gu; Xin Feng; Zhe Wang; Xiangyunong Cao; Mingyao Sun; Zhi Ning; Penggang Zheng; Yuchen Mai; Zijie Xu; Wai Ming Chan; Xin Li; et al. (Atmospheric Environment, 2024)

The breeding ecology of the Agulhas Long-billed Lark: an endemic bird dependent on the remnant Renosterveld of the Western Cape Province, South Africa - Sanjo Rose; Robert Leslie Thomson; Alan Tristam Kenneth Lee; Peter Geoffrey Ryan (Journal of Ornithology, 2024)
The Agulhas Long-billed Lark Certhilauda brevirostris is restricted to the Agulhas Plain, South Africa, a region extensively transformed for crop production and sheep grazing. We present data on nest and egg characteristics, clutch and brood size, parental care and breeding success previously undescribed for this species. During field surveys in 2020 and 2021, 29 nests were located. Of these, 16 were monitored by camera traps. Laying started in late winter (July) and continued until early summer (late November). Most nests (66%) were in Renosterveld, a unique vegetation component of the Fynbos Biome, with the remainder in human-modified landscapes. Female larks were responsible for nest construction and incubation. Both sexes provisioned nestlings, with provisioning rate related to nestling age and time of day but not brood size. Breeding success was low, with only 14% of nests fledging any young. Only one repeat nesting attempt following a predation event was observed, but the attempt was abandoned. Nest predation was the main cause of nest failure, with eight species of nest predators identified. An apparent preference for nesting in Renosterveld highlights the need for protection of this endangered habitat type. As a ground-nesting species in an agriculturally transformed landscape, this lark faces numerous threats associated with habitat loss, altered predation pressure, exposure to pesticides and disturbance at nest sites.

Uncovering the magnitude of African pangolin poaching with extensive nanopore DNA genotyping of seized scales - Darren Yeo; Amy H. J. Chan; Kum Chew Hiong; Jasmine Ong; Jun Yuan Ng; Jie Min Lim; Wendy Zhang; Sara R. Lim; Charlene J. Fernandez; Anna M‐S. Wong; Benjamin P. Y‐H. Lee; Max D. Y. Khoo; et al. (Conservation Biology, 2024)
Trade in pangolins is illegal, and yet tons of their scales and products are seized at various ports. These large seizures are challenging to process and comprehensively genotype for upstream provenance tracing and species identification for prosecution. We implemented a scalable DNA barcoding pipeline in which rapid DNA extraction and MinION sequencing were used to genotype a substantial proportion of pangolin scales subsampled from 2 record shipments seized in Singapore in 2019 (37.5 t). We used reference sequences to match the scales to phylogeographical regions of origin. In total, we identified 2346 cytochrome b ( cytb ) barcodes of white‐bellied ( Phataginus tricuspis ) (from 1091 scales), black‐bellied ( Phataginus tetradactyla ) (227 scales), and giant ( Smutsia gigantea ) (1028 scales) pangolins. Haplotype diversity was higher for P. tricuspis scales (121 haplotypes, 66 novel) than that for P. tetradactyla (22 haplotypes, 15 novel) and S. gigantea (25 haplotypes, 21 novel) scales. Of the novel haplotypes, 74.2% were likely from western and west‐central Africa, suggesting potential resurgence of poaching and newly exploited populations in these regions. Our results illustrate the utility of extensively subsampling large seizures and outline an efficient molecular approach for rapid genetic screening that should be accessible to most forensic laboratories and enforcement agencies.

Toxic dinoflagellate Centrodinium punctatum (Cleve) F.J.R. Taylor: An examination on the responses in growth and toxin contents to drastic changes of temperature and salinity - Hyeon Ho Shin; Zhun Li; Damien Réveillon; Véronique Savar; Philipp Hess; Kenneth Neil Mertens; Joo Yeon Youn; Kyoungsoon Shin; Jihoon Lee; A-Young Shin; Eunjung Byun; Yeong Du Yoo; et al. (Harmful Algae, 2024)

Nutrition Knowledge Is Associated With Diet Quality Among US Army Soldiers - Kenneth A. Sheafer; Dustin M. Lee; Beatriz George; Julianna M. Jayne; Renee E. Cole (Journal of Nutrition Education and Behavior, 2023)

A generic approach to construct pseudo components for oil weathering models - Xiaolong Geng; Christopher H. Barker; Amy MacFadyen; Michel C. Boufadel; Dalina L. Thrift-Viveros; Robert K. Jones; Caitlin O’Connor; Kenneth Lee (Journal of Hazardous Materials, 2023)

Membrane technology for treating decanted oily wastewater from marine oil spill operations: Comparison between membrane filtration and membrane bioreactor - Anisha Bhattacharyya; Lei Liu; Margaret Walsh; Kenneth Lee (Marine Pollution Bulletin, 2023)

Long-term biodegradation of crude oil in high-arctic backshore sediments: The Baffin Island Oil Spill (BIOS) after nearly four decades - Lars Schreiber; Blake Hunnie; Ianina Altshuler; Esteban Góngora; Madison Ellis; Christine Maynard; Julien Tremblay; Jessica Wasserscheid; Nathalie Fortin; Kenneth Lee; Gary Stern; Charles W. Greer (Environmental Research, 2023)

Identification of the driving factors of microplastic load and morphology in estuaries for improving monitoring and management strategies: A global meta-analysis - Qi Feng; Chunjiang An; Zhi Chen; Kenneth Lee; Zheng Wang (Environmental Pollution, 2023)

Fluorescent A2A and A3 adenosine receptor antagonists as flow cytometry probes - Kiran S. Toti; Ryan G. Campbell; Hobin Lee; Veronica Salmaso; R. Rama Suresh; Zhan-Guo Gao; Kenneth A. Jacobson (Purinergic Signalling, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Preparation, characteristics, and performance of the microemulsion system in the removal of oil from beach sand - Huifang Bi; Catherine N. Mulligan; Kenneth Lee; Chunjiang An; Jiyuan Wen; Xiaohan Yang; Linxiang Lyu; Zhaonian Qu (Marine Pollution Bulletin, 2023)

Setting the stage to advance oil toxicity testing: Overview of knowledge gaps, and recommendations - Jennifer R. Loughery; Gina M. Coelho; Kenneth Lee; Benjamin de Jourdan (Aquatic Toxicology, 2023)

Cells in the polyaneuploid cancer cell (PACC) state have increased metastatic potential - Mikaela M. Mallin; Nicholas Kim; Mohammad Ikbal Choudhury; Se Jong Lee; Steven S. An; Sean X. Sun; Konstantinos Konstantopoulos; Kenneth J. Pienta; Sarah R. Amend (Clinical & Experimental Metastasis, 2023)
Although metastasis is the leading cause of cancer deaths, it is quite rare at the cellular level. Only a rare subset of cancer cells (~ 1 in 1.5 billion) can complete the entire metastatic cascade: invasion, intravasation, survival in the circulation, extravasation, and colonization (i.e. are metastasis competent). We propose that cells engaging a Polyaneuploid Cancer Cell (PACC) phenotype are metastasis competent. Cells in the PACC state are enlarged, endocycling (i.e. non-dividing) cells with increased genomic content that form in response to stress. Single-cell tracking using time lapse microscopy reveals that PACC state cells have increased motility. Additionally, cells in the PACC state exhibit increased capacity for environment-sensing and directional migration in chemotactic environments, predicting successful invasion. Magnetic Twisting Cytometry and Atomic Force Microscopy reveal that cells in the PACC state display hyper-elastic properties like increased peripheral deformability and maintained peri-nuclear cortical integrity that predict successful intravasation and extravasation. Furthermore, four orthogonal methods reveal that cells in the PACC state have increased expression of vimentin, a hyper-elastic biomolecule known to modulate biomechanical properties and induce mesenchymal-like motility. Taken together, these data indicate that cells in the PACC state have increased metastatic potential and are worthy of further in vivo analysis.

Field fluorometers for assessing oil dispersion at sea - Charbel Abou-Khalil; Wen Ji; Roger C. Prince; Gina M. Coelho; Tim J. Nedwed; Kenneth Lee; Michel C. Boufadel (Marine Pollution Bulletin, 2023)

Microbial responses to increased salinity in oiled upper tidal shorelines - Charbel Abou-Khalil; Nathalie Fortin; Jessica Wasserscheid; Roger C. Prince; Charles W. Greer; Kenneth Lee; Michel C. Boufadel (International Biodeterioration & Biodegradation, 2023)

Advances to the CROSERF protocol to improve oil spill response decision making - Kenneth Lee; Gina Coelho; Jennifer Loughery; Benjamin de Jourdan (Aquatic Toxicology, 2023)

Biomass Quality Responses to Selection for Increased Biomass Yield in Perennial Energy Grasses - Michael D. Casler; DoKyoung Lee; Robert B. Mitchell; Kenneth J. Moore; Paul R. Adler; R. Mark Sulc; Keith D. Johnson; Robert L. Kallenbach; Arvid R. Boe; Russell D. Mathison; Kim A. Cassida; Doohong Min; et al. (BioEnergy Research, 2023)

Exploring the use of sodium caseinate-assisted responsive separation for the treatment of washing effluents in shoreline oil spill response - Rengyu Yue; Zhibin Ye; Sichen Gao; Yiqi Cao; Kenneth Lee; Chunjiang An; Zhaonian Qu; Shuyan Wan (Science of The Total Environment, 2023)

Performance evaluation of a pilot-scale membrane filtration system for oily wastewater treatment: CFD modeling and scale-up design - Mahsa Keyvan Hosseini; Lei Liu; Parisa Keyvan Hosseini; Kenneth Lee; Jiahe Miao (Journal of Water Process Engineering, 2023)

Development and testing of a 2D offshore oil spill modeling tool (OSMT) supported by an effective calibration method - Zhaoyang Yang; Zhi Chen; Kenneth Lee (Marine Pollution Bulletin, 2023)

Biodegradation potential of residue generated during the in-situ burning of oil in the marine environment - Ruby Pyke; Nathalie Fortin; Jessica Wasserscheid; Julien Tremblay; Lars Schreiber; Marie-Josee Levesque; Stephanie Messina-Pacheco; Lyle Whyte; Feiyue Wang; Kenneth Lee; David Cooper; Charles W. Greer (Journal of Hazardous Materials, 2023)

Adopting a toxic unit model paradigm in design, analysis and interpretation of oil toxicity testing - Thomas F. Parkerton; Deborah French-McCay; Benjamin de Jourdan; Kenneth Lee; Gina Coelho (Aquatic Toxicology, 2023)

An experimental oil spill at a tidal freshwater wetland along the St. Lawrence River re-visited after 21 years - Lars Schreiber; Nathalie Fortin; Alberto Mazza; Christine Maynard; Jessica Wasserscheid; Julien Tremblay; Kenneth Lee; Charles W. Greer (Environmental Research, 2023)

Review of Hollow Fiber (HF) Membrane Filtration Technology for the Treatment of Oily Wastewater: Applications and Challenges - Mahsa Keyvan Hosseini; Lei Liu; Parisa Keyvan Hosseini; Anisha Bhattacharyya; Kenneth Lee; Jiahe Miao; Bing Chen (Journal of Marine Science and Engineering, 2022)
Oily wastewater has been recognized as a threat to the environment due to its hazardous nature and it can negatively affect the ecosystem, and threaten wildlife and human health. Physical, chemical, and biological technologies demonstrated a mixed performance in oily wastewater treatment, and, therefore, a proper treatment technology for oily wastewater needs to be addressed. Membrane filtration using a hollow fiber (HF) membrane is a promising alternative to remove emulsified oil from oily wastewater. This review discusses different sources of oily wastewater, various treatment methods, and membrane technology. The assessment has been focused on the parameters affecting HF membrane performance and applications of HF membrane-based technology to treat oily wastewater. This review paper reveals that HF membrane filtration systems have been previously used for the treatment of oily wastewater in bench-scale studies and few pilot-scale applications, which proved to be favorable in the treatment of recalcitrant wastewater containing oil and high salinity. Limitations associated with membrane fouling and the reduction of membrane permeability and membrane lifespan can be tackled and alleviated through modifying membrane chemistry and adjusting operational parameters. The compilation of studies showed that a low food/microorganism (F/M) ratio, long solid retention time (SRT) with high sludge age, long hydraulic retention time (HRT), and moderate aeration were the preferred operational parameters when treating oily wastewater. Based on this review, future studies should focus on optimizing the hydrodynamic conditions of the HF system, the commercialization of modified HF membranes, and the utilization of green technology in HF membrane construction to broaden HF membrane technology applications.

A Comprehensive Review of Canadian Marine Oil Spill Response System through the Lens of Decanting Regulations and Practices - Naznin Sultana Daisy; Mohammad Hesam Hafezi; Lei Liu; Kenneth Lee (Journal of Marine Science and Engineering, 2022)
Marine oil spill response operations could generate a large volume of liquid oily wastes (e.g., emulsified oil, non-emulsified oil, and wastewater) that can be up to 30 to 40 times greater than the original volume of spilled oil. Oil decanting technologies are used globally for recovering spilled oil and handling liquid wastes. Canada follows the standards set out in the MARPOL 73/78 Annex 1 International regulations in most areas, with more strict discharge requirements in certain locations. For instance, inland waters discharge should not exceed 5 ppm, and in special areas, such as the Great Lakes, the discharge standard is under 0 ppm. In the event of an oil spill, decanted seawater should be barged to shore for disposal, which significantly constrains the response capacity and efficiency of oil recovery by skimmers due to limited temporary storage space in barges and the long time and high cost of transportation. This has become one of the greatest challenges the Canadian governments and oil spill response industries are facing in Canada. Moreover, when the spill response team decides that decanting is an appropriate way to handle the spilled oil, the approval process may take a long time, which negatively impacts the spill that has already occurred. Moreover, Canada uses a 10,000-tonne planning standard for oil spill preparedness, whereas the United States uses a worst-case scenario, and Europe uses a 60,000 m3 planning standard. The existing planning threshold in Canada can cause the country to be not fully prepared when it comes to responding to a very large oil spill if one should occur. This study conducted a comprehensive review of the current Canadian oil spill response system and framework, regulations, roles and responsibilities of federal and provincial governments, existing decanting capabilities, and capacities of Canadian oil spill responders. More importantly, this study identified the gaps in the current oil spill response system and regulatory and technological barriers to oil decanting. Marine oil decanting regulations and practices in the US and selected European countries have also been reviewed to support addressing the challenges and improving the Canadian experience. It is expected that this study would help the stakeholders and professionals to better understand the oil spill response system and oil decanting status quo in Canada and facilitate Canadian governments and industries to better address the challenges in oil spill regulations and practices.

Review of Biological Processes in a Membrane Bioreactor (MBR): Effects of Wastewater Characteristics and Operational Parameters on Biodegradation Efficiency When Treating Industrial Oily Wastewater - Anisha Bhattacharyya; Lei Liu; Kenneth Lee; Jiahe Miao (Journal of Marine Science and Engineering, 2022)
Oily wastewater is generated from various sources within the petrochemical industry, including extraction, refining and processing, storage, and transportation. Over the years, large volumes of oily wastewater from this industry have made their way into the environment, negatively affecting the environment, human health, and the economy. The raw waters from the petrochemical industry can differ significantly and have complex features, making them difficult to treat. Membrane bioreactors (MBR) are a promising treatment option for complex wastewater; it is a combined physical and biological treatment. The biological component of the MBR is one of the main contributing factors to its success. It is important to know how to control the parameters within the bioreactor to promote the biodegradation of hydrocarbons to improve the treatment efficiency of the MBR. There have been many reviews on the effects of the biological factors of membrane fouling; however, none have discussed the biodegradation process in an MBR and its impact on effluent quality. This review paper investigates the hydrocarbon biodegradation process in an aerobic MBR system by gathering and analyzing the recent academic literature to determine how oily wastewater characteristics and operational parameters affect this process.

Application of Phase-Selective Organogelators (PSOGs) for Marine Oil Spill Remediation - Huifang Bi; Chunjiang An; Catherine N. Mulligan; Zhi Chen; Kenneth Lee; Jiyuan Wen; Zhaonian Qu; Xinya Chen (Journal of Marine Science and Engineering, 2022)
Oil spill incidents frequently cause serious impacts on the ecosystem, society, and economy. To cope with this problem, the use of phase-selective organogelators (PSOGs) has been developed in recent years as a promising oil spill response tool, which can congeal oils from biphasic systems, accelerating oil removal and recovery and reducing impacts on the environment. This article systematically reviews reported technologies for the use of PSOGs for potential oil spill remediation in the literature from January 2016 to May 2022. It discusses several kinds of PSOGs based on molecular structures which are possible for gelling oil in the presence of water/seawater. Their mechanisms for phase-selective gelation are summarized, including hydrogen bonding, π–π stacking interactions, van der Waals force, hydrophobic interactions, etc. The currently possible deployment methods for the application of PSOGs are explored; carrier solvents and powder form are frequently used. Moreover, the challenges and the corresponding recommendations regarding standardized testing protocols and evaluation framework, gelation selectivity, as well as challenges in field tests, are further discussed.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Capillary morphogenesis gene 2 (CMG2) mediates growth factor-induced angiogenesis by regulating endothelial cell chemotaxis - Lorna M. Cryan; Tsz-Ming Tsang; Jessica Stiles; Lauren Bazinet; Sai Lun Lee; Samuel Garrard; Erika Madrian; Cody Roberts; Jessie Payne; Andrew Jensen; Arthur E. Frankel; P. Christine Ackroyd; et al. (Angiogenesis, 2022)

Experimental and modeling studies of the effects of nanoclay on the oil behaviors in a water–sand system - Rezvan Iravani; Chunjiang An; Mojtaba Mohammadi; Kenneth Lee; Kaiqiang Zhang (Environmental Science and Pollution Research, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Using knowledge to care for country: Indigenous-led evaluations of research to adaptively co-manage Kakadu National Park, Australia - Cathy J. Robinson; Jennifer Mairi Macdonald; Michael Douglas; Justin Perry; Samantha Setterfield; Dennis Cooper; Maria Lee; Jonathan Nadji; Sean Nadji; Alfred Nayinggul; Anita Nayinggul; Kenneth Mangiru; et al. (Sustainability Science, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Learning Environments and Evidence-Based Practices in Bioengineering and Biomedical Engineering - Kristen Billiar; Donald P. Gaver; Kenneth Barbee; Anita Singh; John D. DesJardins; Beth Pruitt; Joe Tranquillo; Glenn Gaudette; Beth Winkelstein; Lee Makowski; Jennifer R. Amos; Ann Saterbak; et al. (Biomedical Engineering Education, 2022)
This paper provides a synopsis of discussions related to the Learning Environments track of the Fourth BME Education Summit held at Case Western Reserve University in Cleveland, Ohio in May 2019. This summit was organized by the Council of Chairs of Bioengineering and Biomedical Engineering, and participants included over 300 faculty members from 100+ accredited undergraduate programs. The Learning Environments track had six interactive workshops that provided facilitated discussion and provide recommendations in the areas of: (1) Authentic project/problem identification in clinical, industrial, and global settings, (2) Experiential problem/project-based learning within courses, (3) Experiential learning in co-curricular learning settings, (4) Team-based learning, (5) Teaching to reach a diverse classroom, and (6) Innovative platforms and pedagogy. A summary of the findings, best practices and recommendations from each of the workshops is provided under separate headings below, and a list of resources is provided at the end of this paper.

Characteristics of patients discharged and readmitted after COVID-19 hospitalisation within a large integrated health system in the United States - Cheng-Wei Huang; Prashant P. Desai; Kenneth K. Wei; In-Lu Amy Liu; Janet S. Lee; Huong Q. Nguyen (Infectious Diseases, 2021)

Multiscale simulations of left ventricular growth and remodeling - Hossein Sharifi; Charles K. Mann; Alexus L. Rockward; Mohammad Mehri; Joy Mojumder; Lik-Chuan Lee; Kenneth S. Campbell; Jonathan F. Wenk (Biophysical Reviews, 2021)

Remote Ischemic Postconditioning vs. Physical Exercise After Stroke: an Alternative Rehabilitation Strategy? - Xiaokun Geng; Qingzhu Wang; Hangil Lee; Christian Huber; Melissa Wills; Kenneth Elkin; Fengwu Li; Xunming Ji; Yuchuan Ding (Molecular Neurobiology, 2021)
There remain debates on neuroprotection and rehabilitation techniques for acute ischemic stroke patients. Therapeutic physical exercise following stroke has shown promise but is challenging to apply clinically. Ischemic conditioning, which has several clinical advantages, is a potential neuroprotective method for stroke rehabilitation that is less understood. In the present study, the rehabilitative properties and mechanisms of physical exercise and remote ischemic postconditioning (RIPostC) after stroke were compared and determined. A total of 248 adult male Sprague-Dawley rats were divided into five groups: (1) sham, (2) stroke, (3) stroke with intense treadmill exercise, (4) stroke with mild treadmill exercise, and (5) stroke with RIPostC. Focal ischemia was evaluated by infarct volume and neurological deficit. Long-term functional outcomes were represented through neurobehavioral function tests: adhesive removal, beam balance, forelimb placing, grid walk, rota-rod, and Morris water maze. To further understand the mechanisms underlying neurorehabilitation and verify the presence thereof, we measured mRNA and protein levels of neuroplasticity factors, synaptic proteins, angiogenesis factors, and regulation molecules, including HIF-1α, BDNF, TrkB, and CREB. The key role of HIF-1α was elucidated by using the inhibitor, YC-1. Both exercise intensities and RIPostC significantly decreased infarct volumes and neurological deficits and outperformed the stroke group in the neurobehavioral function tests. All treatment groups showed significant increases in mRNA and protein expression levels of the target molecules for neurogenesis, synaptogenesis, and angiogenesis, with intermittent further increases in the RIPostC group. HIF-1α inhibition nullified most beneficial effects and indicative molecule expressions, including HIF-1α, BDNF, TrkB, and CREB, in both procedures. RIPostC is equally, or superiorly, effective in inducing neuroprotection and rehabilitation compared to exercise in ischemic rats. HIF-1α likely plays an important role in the efficacy of neuroplasticity conditioning, possibly through HIF-1α/BDNF/TrkB/CREB regulation.

Exploring the effects of microalgal biomass on the oil behavior in a sand-water system - Azar Vahabisani; Chunjiang An; Xiaying Xin; Edward Owens; Kenneth Lee (Environmental Science and Pollution Research, 2021)

Factors influencing the fate of oil spilled on shorelines: a review - Zheng Wang; Chunjiang An; Kenneth Lee; Edward Owens; Zhi Chen; Michel Boufadel; Elliott Taylor; Qi Feng (Environmental Chemistry Letters, 2021)

Space–time variations of sea ice in Bohai Sea in the winter of 2009–2010 simulated with a coupled ocean and ice model - Rui Li; Youyu Lu; Xianmin Hu; Donglin Guo; Peng Zhao; Ning Wang; Kenneth Lee; Baiyu Zhang (Journal of Oceanography, 2021)

Modeling oil dispersion under breaking waves. Part II: Coupling Lagrangian particle tracking with population balance model - Fangda Cui; Lin Zhao; Cosan Daskiran; Thomas King; Kenneth Lee; Joseph Katz; Michel C. Boufadel (Environmental Fluid Mechanics, 2020)

Modeling oil dispersion under breaking waves. Part I: Wave hydrodynamics - Fangda Cui; Cosan Daskiran; Thomas King; Brian Robinson; Kenneth Lee; Joseph Katz; Michel C. Boufadel (Environmental Fluid Mechanics, 2020)

Biomass Production of Prairie Cordgrass (Spartina pectinata Link.) Using Urea and Kura Clover (Trifolium ambiguum Bieb.) as a Source of Nitrogen - SungUn Kim; Kenneth Albrecht; Craig Sheaffer; Dokyoung Lee; Senthil Subramanian; Vance Owens (BioEnergy Research, 2020)
Optimizing nitrogen (N) management is an important factor for sustainable perennial biomass systems. However, N application is costly, both financially and environmentally. Our objectives were to determine: (1) N rate and plant spacing effects on yield and yield components of prairie cordgrass swards and (2) fertilizer N replacement value (FNRV) of kura clover in prairie cordgrass-kura clover binary mixtures. Plots were established in Illinois, Minnesota, South Dakota, and Wisconsin, USA, in 2010. Kura clover was transplanted on 30-cm centers in all treatments in which it was a component; prairie cordgrass seedlings were transplanted within the kura clover on 60- and 90-cm centers. Monoculture prairie cordgrass stands were established at the same population densities of mixed stands and fertilized with 0, 75, 150, or 225 kg N ha -1 . Biomass was harvested in the autumn from 2011 to 2013. N (urea), year, plant spacing, and year × plant spacing affected prairie cordgrass production at all locations. Prairie cordgrass yield increased with N application, but the response varied by location. N application tended to increase prairie cordgrass tiller density and consistently increased tiller mass. Prairie cordgrass yield with 0 N was equal to or less than the yield of prairie cordgrass/kura clover mixtures at all locations in 2011 and 2012; however, kura clover provided a FNRV of 25–82 kg N ha -1 to prairie cordgrass in 2013. Kura clover has potential to provide N to prairie cordgrass in binary mixtures of these two species and on land that may not be easily farmed due to wetness.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Capacity challenges in water quality monitoring: understanding the role of human development - Sabrina Kirschke; Tamara Avellán; Ilona Bärlund; Janos J. Bogardi; Laurence Carvalho; Deborah Chapman; Chris W. S. Dickens; Kenneth Irvine; SungBong Lee; Thomas Mehner; Stuart Warner (Environmental Monitoring and Assessment, 2020)
Monitoring the qualitative status of freshwaters is an important goal of the international community, as stated in the Sustainable Development Goal (SDGs) indicator 6.3.2 on good ambient water quality. Monitoring data are, however, lacking in many countries, allegedly because of capacity challenges of less-developed countries. So far, however, the relationship between human development and capacity challenges for water quality monitoring have not been analysed systematically. This hinders the implementation of fine-tuned capacity development programmes for water quality monitoring. Against this background, this study takes a global perspective in analysing the link between human development and the capacity challenges countries face in their national water quality monitoring programmes. The analysis is based on the latest data on the human development index and an international online survey amongst experts from science and practice. Results provide evidence of a negative relationship between human development and the capacity challenges to meet SDG 6.3.2 monitoring requirements. This negative relationship increases along the course of the monitoring process, from defining the enabling environment, choosing parameters for the collection of field data, to the analytics and analysis of five commonly used parameters (DO, EC, pH, TP and TN). Our assessment can be used to help practitioners improve technical capacity development activities and to identify and target investment in capacity development for monitoring.

Correction to: Development of Decisional Values Statements for Lung Cancer Screening among African American Smokers - Randi M. Williams; Kenneth H. Beck; James Butler; Sunmin Lee; Min Qi Wang; Kathryn L. Taylor; Cheryl L. Knott (Journal of Cancer Education, 2020)

Development of Decisional Values Statements for Lung Cancer Screening Among African American Smokers - Randi M. Williams; Kenneth H. Beck; James Butler; Sunmin Lee; Min Qi Wang; Kathryn L. Taylor; Cheryl L. Knott (Journal of Cancer Education, 2020)

Oil Droplet Dispersion under a Deep-Water Plunging Breaker: Experimental Measurement and Numerical Modeling - Fangda Cui; Xiaolong Geng; Brian Robinson; Thomas King; Kenneth Lee; Michel C. Boufadel (Journal of Marine Science and Engineering, 2020)
Knowledge of the droplet size distribution (DSD) of spilled oil is essential for the accurate prediction of oil transport, dissolution, and biodegradation. Breaking waves play important roles in oil droplet formation in oceanic environments. To understand the effects of breaking waves on oil DSD, oil spill experiments were designed and performed in a large-scale wave tank. A plunging breaker with a height of about 0.4 m was produced using the dispersive focusing method within the tank. Oil placed within the breaker resulted in a DSD that was measured using a shadowgraph camera and found to fit a Gaussian distribution N (µ = 1.2 mm, σ2 = 0.29 mm2). For droplets smaller than 1500 µm, the number-based DSD matched the DS1988 correlation, which gives N(d) ~ d−2.3, but this was N(d) ~ d−9.7 for droplets larger than 1500 µm. An order of magnitude investigation revealed that a Gaussian volume-based DSD results in a number-based DSD that may be approximated by d−b (with b ≈ 2) for small diameters (relative to the mean), which explains the occurrence of the DS1988 correlation. With the measured wave hydrodynamics, the VDROP model was adopted to simulate the DSD, which closely matched the observed DSD. The present results reduce the empiricism of the DS1988 correlation.

Nitrogen Demand Associated with Increased Biomass Yield of Switchgrass and Big Bluestem: Implications for Future Breeding Strategies - Michael D. Casler; DoKyoung Lee; Robert B. Mitchell; Paul R. Adler; R. Mark Sulc; Keith D. Johnson; Robert L. Kallenbach; Arvid R. Boe; Russell D. Mathison; Kim A. Cassida; Doohong Min; Kenneth J. Moore (BioEnergy Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

A Review on the Factors Affecting the Deposition, Retention, and Biodegradation of Oil Stranded on Beaches and Guidelines for Designing Laboratory Experiments - Michel Boufadel; Xiaolong Geng; Chunjiang An; Edward Owens; Zhi Chen; Kenneth Lee; Elliott Taylor; Roger C. Prince (Current Pollution Reports, 2019)

Evaluation of CMIP5 ability to reproduce twentieth century regional trends in surface air temperature and precipitation over CONUS - Jinny Lee; Duane Waliser; Huikyo Lee; Paul Loikith; Kenneth E. Kunkel (Climate Dynamics, 2019)

Metagenomic and metatranscriptomic responses of natural oil degrading bacteria in the presence of dispersants - Julien Tremblay; Nathalie Fortin; Miria Elias; Jessica Wasserscheid; Thomas L. King; Kenneth Lee; Charles W. Greer (Environmental Microbiology, 2019)
Summary Oil biodegradation has been extensively studied in the wake of the deepwater horizon spill, but the application of dispersant to oil spills in marine environments remains controversial. Here, we report metagenomic (MG) and metatranscriptomic (MT) data mining from microcosm experiments investigating the oil degrading potential of Canadian west and east coasts to estimate the gene abundance and activity of oil degrading bacteria in the presence of dispersant. We found that the addition of dispersant to crude oil mainly favours the abundance of Thalassolituus in the summer and Oleispira in the winter, two key natural oil degrading bacteria. We found a high abundance of genes related not only to n ‐alkane and aromatics degradation but also associated with transporters, two‐component systems, bacterial motility, secretion systems and bacterial chemotaxis.

The urgent need for microbiology literacy in society - Kenneth Timmis; Ricardo Cavicchioli; José Luis Garcia; Balbina Nogales; Max Chavarría; Lisa Stein; Terry J. McGenity; Nicole Webster; Brajesh K. Singh; Jo Handelsman; Victor de Lorenzo; Carla Pruzzo; et al. (Environmental Microbiology, 2019)

Fine mapping of qGL5H, a major grain length locus in barley (Hordeum vulgare L.) - Calum Watt; Gaofeng Zhou; Lee-Anne McFawn; Kenneth James Chalmers; Chengdao Li (Theoretical and Applied Genetics, 2019)

Quantifying the agreement between observed and simulated extratropical modes of interannual variability - Jiwoo Lee; Kenneth R. Sperber; Peter J. Gleckler; Céline J. W. Bonfils; Karl E. Taylor (Climate Dynamics, 2019)

Evaluation of multi-decadal UCLA-CFSv2 simulation and impact of interactive atmospheric-ocean feedback on global and regional variability - Jiwoo Lee; Yongkang Xue; Fernando De Sales; Ismaila Diallo; Larry Marx; Michael Ek; Kenneth R. Sperber; Peter J. Gleckler (Climate Dynamics, 2019)

Estimating the Usefulness of Chemical Dispersant to Treat Surface Spills of Oil Sands Products - Thomas King; Brian Robinson; Scott Ryan; Kenneth Lee; Michel Boufadel; Jason Clyburne (Journal of Marine Science and Engineering, 2018)
This study examines the use of chemical dispersant to treat an oil spill after the initial release. The natural and chemically enhanced dispersion of four oil products (dilbit, dilynbit, synbit and conventional crude) were investigated in a wave tank. Experiments were conducted in spring and summer to capture the impact of temperature, and the conditions in the tank were of breaking waves with a wave height of 0.4 m. The results showed that natural dispersion effectiveness (DE) was less than 10%. But the application of dispersant increased the DE by an order of magnitude with a statistically significant level (p

Polymorphic and Covalent Transformations of Gabapentin in Binary Excipient Mixtures after Milling-Induced Stress - Radaduen Tinmanee; Stephen D. Stamatis; Eji Ueyama; Kenneth R. Morris; Lee E. Kirsch (Pharmaceutical Research, 2018)

Genetic diversity patterns in ex situ collections of Oryza officinalis Wall. ex G. Watt revealed by morphological and microsatellite markers - Maria Elizabeth Boncodin Naredo; Sheila Mae Quilloy Mercado; Maria Celeste Naynes Banaticla-Hilario; Myrricar Loren Berdos; Mario Alcantara Rodriguez; Kenneth Lee McNally; Ruaraidh Sackville Hamilton (Genetic Resources and Crop Evolution, 2017)

Preventive Effects of Poloxamer 188 on Muscle Cell Damage Mechanics Under Oxidative Stress - Sing Wan Wong; Yifei Yao; Ye Hong; Zhiyao Ma; Stanton H. L. Kok; Shan Sun; Michael Cho; Kenneth K. H. Lee; Arthur F. T. Mak (Annals of Biomedical Engineering, 2017)

Telmisartan increases systemic exposure to rosuvastatin after single and multiple doses, and in vitro studies show telmisartan inhibits ABCG2-mediated transport of rosuvastatin - Miao Hu; Hon-Kit Lee; Kenneth K. W. To; Benny S. P. Fok; Siu-Kwan Wo; Chung-Shun Ho; Chun-Kwok Wong; Zhong Zuo; Thomas Y. K. Chan; Juliana C. N. Chan; Brian Tomlinson (European Journal of Clinical Pharmacology, 2016)

Effects of food restriction on expression of place conditioning and biochemical correlates in rat nucleus accumbens - Caroline Jung; Ariana Rabinowitsch; Wei Ting Lee; Danielle Zheng; Soledad Cabeza de Vaca; Kenneth D. Carr (Psychopharmacology, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Preserved emotional awareness of pain in a patient with extensive bilateral damage to the insula, anterior cingulate, and amygdala - Justin S. Feinstein; Sahib S. Khalsa; Tim V. Salomons; Kenneth M. Prkachin; Laura A. Frey-Law; Jennifer E. Lee; Daniel Tranel; David Rudrauf (Brain Structure and Function, 2016)

Prioritization of knowledge needs for sustainable aquaculture: a national and global perspective - Aisla C Jones; Angela Mead; Michel J Kaiser; Melanie C V Austen; Alex W Adrian; Neil A Auchterlonie; Kenneth D Black; Lucy R Blow; Charlotte Bury; Janet H Brown; Gavin M Burnell; Elaine Connolly; et al. (Fish and Fisheries, 2015)
Aquaculture is currently the fastest expanding global animal food production sector and is a key future contributor to food security. An increase in food security will be dependent upon the development and improvement of sustainable practices. A prioritization exercise was undertaken, focusing on the future knowledge needs to underpin UK sustainable aquaculture (both domestic and imported products) using a ‘task force’ group of 36 ‘practitioners’ and 12 ‘research scientists’ who have an active interest in sustainable aquaculture. A long list of 264 knowledge needs related to sustainable aquaculture was developed in conjunction with the task force. The long list was further refined through a three stage process of voting and scoring, including discussions of each knowledge need. The top 25 knowledge needs are presented, as scored separately by ‘practitioners’ or ‘research scientists’. There was similar agreement in priorities identified by these two groups. The priority knowledge needs will provide guidance to structure ongoing work to make science accessible to practitioners and help to prioritize future science policy needs and funding. The process of knowledge exchange, and the mechanisms by which this can be achieved, effectively emerged as the top priority for sustainable aquaculture. Viable alternatives to wild fish‐based aquaculture feeds, resource constraints that will potentially limit expansion of aquaculture, sustainable offshore aquaculture and the treatment of sea lice also emerged as strong priorities. Although the exercise was focused on UK needs for sustainable aquaculture, many of the emergent issues are considered to have global application.

Characterization of the microbial community structure and the physicochemical properties of produced water and seawater from the Hibernia oil production platform - C. William Yeung; Kenneth Lee; Susan Cobanli; Tom King; Jay Bugden; Lyle G. Whyte; Charles W. Greer (Environmental Science and Pollution Research, 2015)

Oxidative Stress and Plasma Membrane Repair in Single Myoblasts After Femtosecond Laser Photoporation - Xinxing Duan; Kam Tai Chan; Kenneth K. H. Lee; Arthur F. T. Mak (Annals of Biomedical Engineering, 2015)

A blood spot method for detecting fumonisin-induced changes in putative sphingolipid biomarkers in LM/Bc mice and humans - Ronald T. Riley; Jency L. Showker; Christine M. Lee; Cody E. Zipperer; Trevor R. Mitchell; Kenneth A. Voss; Nicholas C. Zitomer; Olga Torres; Jorge Matute; Simon G. Gregory; Allison E. Ashley-Koch; Joyce R. Maddox; et al. (Food Additives & Contaminants: Part A, 2015)

H2O2 Exposure Affects Myotube Stiffness and Actin Filament Polymerization - Sing Wan Wong; Shan Sun; Michael Cho; Kenneth K. H. Lee; Arthur F. T. MAK (Annals of Biomedical Engineering, 2015)

Multimodel ensembles of wheat growth: many models are better than one - Pierre Martre; Daniel Wallach; Senthold Asseng; Frank Ewert; James W. Jones; Reimund P. Rötter; Kenneth J. Boote; Alex C. Ruane; Peter J. Thorburn; Davide Cammarano; Jerry L. Hatfield; Cynthia Rosenzweig; et al. (Global Change Biology, 2015)
Crop models of crop growth are increasingly used to quantify the impact of global changes due to climate or crop management. Therefore, accuracy of simulation results is a major concern. Studies with ensembles of crop models can give valuable information about model accuracy and uncertainty, but such studies are difficult to organize and have only recently begun. We report on the largest ensemble study to date, of 27 wheat models tested in four contrasting locations for their accuracy in simulating multiple crop growth and yield variables. The relative error averaged over models was 24–38% for the different end‐of‐season variables including grain yield ( GY ) and grain protein concentration ( GPC ). There was little relation between error of a model for GY or GPC and error for in‐season variables. Thus, most models did not arrive at accurate simulations of GY and GPC by accurately simulating preceding growth dynamics. Ensemble simulations, taking either the mean (e‐mean) or median (e‐median) of simulated values, gave better estimates than any individual model when all variables were considered. Compared to individual models, e‐median ranked first in simulating measured GY and third in GPC . The error of e‐mean and e‐median declined with an increasing number of ensemble members, with little decrease beyond 10 models. We conclude that multimodel ensembles can be used to create new estimators with improved accuracy and consistency in simulating growth dynamics. We argue that these results are applicable to other crop species, and hypothesize that they apply more generally to ecological system models.

Ecotoxicity of triphenyltin on the marine copepod Tigriopus japonicus at various biological organisations: from molecular to population-level effects - Andy Xianliang Yi; Jeonghoon Han; Jae-Seong Lee; Kenneth M. Y. Leung (Ecotoxicology, 2014)

Overexpression of SaRBP1 enhances tolerance of Arabidopsis to salt stress - Selvam Ayarpadikannan; Eun Sook Chung; Hyun Ah So; Kyoung Mi Kim; Kenneth Ryan Schraufnagle; Jai Heon Lee (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Floral diversity assessment in Alno communal mixed forest in Benguet, Philippines - Roscinto Ian C. Lumbres; Jennifer A. Palaganas; Sheryll C. Micosa; Kenneth A. Laruan; Elvira D. Besic; Chung-Weon Yun; Young-Jin Lee (Landscape and Ecological Engineering, 2014)

Anti-apoptotic protein BRE/BRCC45 attenuates apoptosis through maintaining the expression of caspase inhibitor XIAP in mouse Lewis lung carcinoma D122 cells - Yiu-Loon Chui; Chun-Hung Ma; Wei Li; Zhenyu Xu; Yao Yao; Frances Ka-Yin Lin; John Yeuk-Hon Chan; Kenneth Ka-Ho Lee (Apoptosis, 2014)

RsERF1 derived from wild radish (Raphanus sativus) confers salt stress tolerance in Arabidopsis - Selvam Ayarpadikannan; Eunsook Chung; Kyoungmi Kim; Hyun-Ah So; Kenneth Ryan Schraufnagle; Jai-Heon Lee (Acta Physiologiae Plantarum, 2014)

Evaluation of Numerical Modeling Methods for the Management of Produced Water Discharges in the Coastal Region with a Canadian Case Study - Lin Zhao; Zhi Chen; Kenneth Lee (Environmental Modeling & Assessment, 2014)

Water deficit affects plant and soil water status, plant growth, and ginsenoside contents in American ginseng - Jinwook Lee; Kenneth W. Mudge (Horticulture, Environment, and Biotechnology, 2013)

Gypsum effects on plant growth, nutrients, ginsenosides, and their relationship in American ginseng - Jinwook Lee; Kenneth W. Mudge (Horticulture, Environment, and Biotechnology, 2013)

Thermal environment shapes cuticle melanism and melanin-based immunity in the ground cricket Allonemobius socius - Kenneth M. Fedorka; Vivian Lee; Wade E. Winterhalter (Evolutionary Ecology, 2013)

The 2011–2016 Transdisciplinary Research on Energetics and Cancer (TREC) Initiative: Rationale and Design - Ruth E. Patterson; Graham A. Colditz; Frank B. Hu; Kathryn H. Schmitz; Rexford S. Ahima; Ross C. Brownson; Kenneth R. Carson; Jorge E. Chavarro; Lewis A. Chodosh; Sarah Gehlert; Jeff Gill; Karen Glanz; et al. (Cancer Causes & Control, 2013)

Predicting family-wide consensus sequence of pre-mRNA splicing signals in legumes and their potential utility as phylogenetic markers - Hong-Kyu Choi; Chae-Young Lee; Goon-Bo Kim; Young-Woo Nam; Kenneth R. Schraufnagle; Young-Soo Chung; Jai-Heon Lee; Doh-Hoon Kim; Ho-Won Jung (Plant Biotechnology Reports, 2013)

Time-dependent changes in glucose and insulin regulation during intermittent hypoxia and continuous hypoxia - Euhan J. Lee; Laura C. Alonso; Darko Stefanovski; Hilary C. Strollo; Lia C. Romano; Baobo Zou; Srikanth Singamsetty; Keith A. Yester; Kenneth R. McGaffin; Adolfo Garcia-Ocana; Christopher P. O’Donnell (European Journal of Applied Physiology, 2013)

Simulation of the intraseasonal variability over the Eastern Pacific ITCZ in climate models - Xianan Jiang; Duane E. Waliser; Daehyun Kim; Ming Zhao; Kenneth R. Sperber; William F. Stern; Siegfried D. Schubert; Guang J. Zhang; Wanqiu Wang; Marat Khairoutdinov; Richard B. Neale; Myong-In Lee (Climate Dynamics, 2012)

Food Web Structure of the Alaskan Nearshore Shelf and Estuarine Lagoons of the Beaufort Sea - Kenneth H. Dunton; Susan V. Schonberg; Lee W. Cooper (Estuaries and Coasts, 2012)

Identification and quantification of aquatic vegetation with hyperspectral remote sensing in western Nevada rivers, USA - Baek Soo Lee; Kenneth C. McGwire; Christian H. Fritsen (International Journal of Remote Sensing, 2011)

Dipyridamole Treatment Prior to Stroke Onset: Examining Post-stroke Cerebral Circulation and Outcome in Rabbits - Christopher D. d’Esterre; Kenneth M. Tichauer; Richard I. Aviv; Wolfgang Eisert; Ting-Yim Lee (Translational Stroke Research, 2011)

Alterations in brain metabolism during the first year of HIV infection - Margaret R. Lentz; Woong-Ki Kim; Hyun Kim; Caroline Soulas; Vallent Lee; Nagagopal Venna; Elkan F. Halpern; Eric S. Rosenberg; Kenneth Williams; R. G. González (Journal of NeuroVirology, 2011)

Modelling the Transport of Oil–Mineral-Aggregates (OMAs) in the Marine Environment and Assessment of Their Potential Risks - Haibo Niu; Zhengkai Li; Kenneth Lee; Paul Kepkay; Joseph V. Mullin (Environmental Modeling & Assessment, 2011)

Ligand-Binding Mass Spectrometry to Study Biotransformation of Fusion Protein Drugs and Guide Immunoassay Development: Strategic Approach and Application to Peptibodies Targeting the Thrombopoietin Receptor - Michael P. Hall; Colin Gegg; Kenneth Walker; Christopher Spahr; Robert Ortiz; Vimal Patel; Steven Yu; Liana Zhang; Hsieng Lu; Binodh DeSilva; Jean W. Lee (The AAPS Journal, 2010)

C4 protein of Beet severe curly top virus is a pathomorphogenetic factor in Arabidopsis - Jungan Park; Hyun-Sik Hwang; Kenneth J. Buckley; Jong-Bum Park; Chung-Kyun Auh; Dong-Giun Kim; Sukchan Lee; Keith R. Davis (Plant Cell Reports, 2010)

Doubling the chromosome number of bahiagrass via tissue culture - Kenneth H. Quesenberry; Judith M. Dampier; Y. Y. Lee; Rex L. Smith; Carlos A. Acuña (Euphytica, 2010)

Differential expression of a novel gene BRE (TNFRSF1A modulator/BRCC45) in response to stress and biological signals - John Yeuk-Hon Chan; Li Li; Ji Miao; Dong-Qing Cai; Kenneth Ka-Ho Lee; Yiu-Loon Chui (Molecular Biology Reports, 2010)

Electricity generation coupled to oxidation of propionate in a microbial fuel cell - Jae Kyung Jang; In Seop Chang; Hwa Yeon Hwang; Yeng Fung Choo; JiYoung Lee; Kyung Suk Cho; Byung Hong Kim; Kenneth H. Nealson (Biotechnology Letters, 2010)

Development of polymorphic microsatellite DNA markers from the Korean field mouse, Apodemus peninsulae - Soo Hyung Eo; Woo-Shin Lee; Travis C. Glenn; Kenneth L. Jones; Eun-Jae Lee; Yong-Su Park; John P. Carroll; Shin-Jae Rhim (Conservation Genetics, 2009)

A peroxynitrite complex of copper: formation from a copper–nitrosyl complex, transformation to nitrite and exogenous phenol oxidative coupling or nitration - Ga Young Park; Subramanian Deepalatha; Simona C. Puiu; Dong-Heon Lee; Biplab Mondal; Amy A. Narducci Sarjeant; Diego del Rio; Monita Y. M. Pau; Edward I. Solomon; Kenneth D. Karlin (JBIC Journal of Biological Inorganic Chemistry, 2009)

Role of Convective Flow in Carmustine Delivery to a Brain Tumor - Davis Yohanes Arifin; Kam Yiu Timothy Lee; Chi-Hwa Wang; Kenneth A. Smith (Pharmaceutical Research, 2009)

Modeling the dispersion of drilling muds using the bblt model: the effects of settling velocity - Haibo Niu; Adam Drozdowski; Tahir Husain; Brian Veitch; Neil Bose; Kenneth Lee (Environmental Modeling & Assessment, 2009)

A highly selective, orally bioavailable, vascular endothelial growth factor receptor-2 tyrosine kinase inhibitor has potent activity in vitro and in vivo - Kenneth R. LaMontagne; Jeannene Butler; Virna B. Borowski; Angel R. Fuentes-Pesquera; Jonathan M. Blevitt; Shenlin Huang; Ronghua Li; Peter J. Connolly; Lee M. Greenberger (Angiogenesis, 2009)

The impact of chemical lateral boundary conditions on CMAQ predictions of tropospheric ozone over the continental United States - Youhua Tang; Pius Lee; Marina Tsidulko; Ho-Chun Huang; Jeffery T. McQueen; Geoffrey J. DiMego; Louisa K. Emmons; Robert B. Pierce; Anne M. Thompson; Hsin-Mu Lin; Daiwen Kang; Daniel Tong; et al. (Environmental Fluid Mechanics, 2009)

The complete nucleotide sequence of the cassava (Manihot esculenta) chloroplast genome and the evolution of atpF in Malpighiales: RNA editing and multiple losses of a group II intron - Henry Daniell; Kenneth J. Wurdack; Anderson Kanagaraj; Seung-Bum Lee; Christopher Saski; Robert K. Jansen (Theoretical and Applied Genetics, 2008)

Numerical modeling of contaminant transport resulting from dissolution of a coal-tar pool in an experimental aquifer - Kenneth Y. Lee; Johannes Khinast; Jung-Hoon Kim (Hydrogeology Journal, 2007)

Non-Invasive Serological Detection of Helicobacter pylori Antigens in Adult Hong Kong Chinese Non-Ulcer Dyspepsia Patients - Vivian W.Y. Lee; Andrew K.W. Chan; Kenneth K.C. Lee; Francis K.L. Chan (Current Microbiology, 2007)

Biostimulation for the Treatment of an oil-contaminated Coastal Salt Marsh - Susana Garcia-Blanco; Albert D. Venosa; Makram T. Suidan; Kenneth Lee; Susan Cobanli; John R. Haines (Biodegradation, 2006)

Absence of CYP2B6 promoter −82T>C mutation in Chinese as an additional factor for slow metabolism of drugs commonly used in infections - Ming-liang He; CK Lin; Kenneth Tong; Bingying Xu; Joseph JY Sung; Hsiang-fu Kung; Shui-shan Lee (European Journal of Clinical Pharmacology, 2006)

Reliability and Validity of an Assessment of Usual Phytoestrogen Consumption (United States) - Pamela L. Horn-Ross; Stephen Barnes; Valerie S. Lee; Christine N. Collins; Peggy Reynolds; Marion M. Lee; Susan L. Stewart; Alison J. Canchola; Landon Wilson; Kenneth Jones (Cancer Causes & Control, 2006)

Dormant Season Prescribed Fire as a Management Tool for the Control of Salix caroliniana Michx. in a Floodplain Marsh - Mary Ann B. Lee; Kenneth L. Snyder; Patricia Valentine-Darby; Steven J. Miller; Kimberli J. Ponzio (Wetlands Ecology and Management, 2005)

Improving Map Accuracy of Soil Variables Using Soil Electrical Conductivity as a Covariate - Alison B. Tarr; Kenneth J. Moore; Donald G. Bullock; Philip M. Dixon; C. Lee Burras (Precision Agriculture, 2005)

Fluoxetine, but not other selective serotonin uptake inhibitors, increases norepinephrine and dopamine extracellular levels in prefrontal cortex - Frank P. Bymaster; Wei Zhang; Petra A. Carter; Janice Shaw; Eyassu Chernet; Lee Phebus; David T. Wong; Kenneth W. Perry (Psychopharmacology, 2002)

The Northeast Pacific GLOBEC Program: Coastal Gulf of Alaska - Thomas Weingartner; Kenneth Coyle; Bruce Finney; Russell Hopcroft; Terry Whitledge; Richard Brodeur; Michael Dagg; Edward Farley; Dale Haidvogel; Lew Haldorson; Al Hermann; Sarah Hinckley; et al. (Oceanography, 2002)

Increased incidence of dyskinesias and other behavioral effects of re-exposure to neuroleptic treatment in social colonies of Cebus apella monkeys - Gary S. Linn; Kenneth Lifshitz; Robert T. O'Keeffe; Kai Lee; Janet Camp-Lifshitz (Psychopharmacology, 2001)

Modeling the Transport of Contaminants Originating from the Dissolution of DNAPL Pools in Aquifers in the Presence of Dissolved Humic Substances - Michael E. Tatalovich; Kenneth Y. Lee; Constantinos V. Chrysikopoulos (Transport in Porous Media, 2000)

Aryl Ester Prodrugs of Cyclic HPMPC. I: Physicochemical Characterization and In Vitro Biological Stability - Reza Oliyai; Jeng-Pyng Shaw; Cathy M. Sueoka-Lennen; Kenneth C. Cundy; Murty N. Arimilli; Robert J. Jones; William A. Lee (Pharmaceutical Research, 1999)

Inorganic nitrogen acquisition in the seagrass Thalassia testudinum: Development of a whole‐plant nitrogen budget - Kun-Seop Lee; Kenneth H Dunton (Limnology and Oceanography, 1999)
Whole‐plant nitrogen (N) uptake experiments were used to quantify the N budget of Thalassia testudinum growing under different sediment nutrient regimes at two locations in the western Gulf of Mexico. At both sites, Corpus Christi Bay (CCB) and lower Laguna Madre (LLM), Texas, concurrent measurements of plant biomass and levels of dissolved inorganic nitrogen (DIN) in the water column and sediments were made over a 12–month period (October 1996–October 1997). Water‐column NH 4 + and NO 3 − + NO 2 ‐ concentrations were not significantly different between study sites (ca. 1.2 µM [NH 4 + ] and 0.7 µM [NO 3 − + NO ] at both sites), but sediment NH 4 + concentrations in CCB (87 µM) were significantly higher than in LLM (26 µM). The higher sediment NH 4 + levels at CCB correlated with significantly higher leaf biomass at CCB, but there was no difference in root biomass between study sites. Leaf NH 4 + uptake showed clear seasonal variation: Vmax was highest in summer and fall, but Km was highest in winter. Vmax of leaf NO 3 ‐ uptake did not change with season, but Km decreased with increasing incubation temperature. There were no clear differences in leaf NH 4 + and NO 3 − uptake rates between study sites, although leaf NH 4 + uptake affinity was higher than that of NO 3 − . Root NH 4 + uptake was variable with season and did not saturate at the experimental NH 4 + concentrations at either site (0–300 µM). Based on these measurements, N acquisition was highest during summer and fall and lowest during winter and spring. Roots and leaves contributed nearly equally to total plant N acquisition (root NH 4 + = 52%; leaf NH 4 + = 38%; and leaf NO 3 − = 10%) at both sites. Annual N acquisition in CCB was double that of LLM (97.03 and 53.49 g N m −2 yr −1 , respectively), but >50% of N uptake was not incorporated into biomass at either site. DIN turnover time ranged from 0.21 to 0.91 d in the water column and from 0.95 to 1.75 d in sediment pore water, indicating the importance of DIN regeneration processes for supporting seagrass production. The similarity in the relative tissue contributions between plants at both sites, despite a significant difference in sediment NH 4 + pool sizes, results from the higher fraction of biomass allocated to below‐ground tissues in plants living under low‐sediment N conditions (LLM). In N‐sufficient sediments, overall plant productivity is greater as T. testudinum is able to allocate a greater proportion of its biomass into photosynthetic aboveground tissues.

Cryo-electron microscopy of GDP-tubulin rings - William V. Nicholson; Minou Lee; Kenneth H. Downing; Eva Nogales (Cell Biochemistry and Biophysics, 1999)

A global survey of haplotype frequencies and linkage disequilibrium at the DRD2 locus - Kenneth K. Kidd; Bharti Morar; Carmela M. Castiglione; Hongyu Zhao; Andrew J. Pakstis; William C. Speed; Batsheva Bonne-Tamir; Ru-Band Lu; David Goldman; Chaeyoung Lee; Yong Suk Nam; David K. Grandy; et al. (Human Genetics, 1998)

Stability of Alkoxycarbonylamidine Prodrugs - Zahra Shahrokh; Eric Lee; Alan G. Olivero; Regina A. Matamoros; Kirk D. Robarge; Arthur Lee; Kenneth J. Weise; Brent K. Blackburn; Michael F. Powell (Pharmaceutical Research, 1998)

Metabolism and Pharmacokinetics of Novel Oral Prodrugs of 9-[(R)-2-(phosphonomethoxy)propyl]adenine (PMPA) in Dogs - Jeng-Pyng Shaw; Cathy M. Sueoka; Reza Oliyai; William A. Lee; Murty N. Arimilli; Choung U. Kim; Kenneth C. Cundy (Pharmaceutical Research, 1997)

Water Quality Functions of Riparian Forest Buffers in Chesapeake Bay Watersheds - Richard Lowrance; Lee S. Altier; J. Denis Newbold; Ronald R. Schnabel; Peter M. Groffman; Judith M. Denver; David L. Correll; J. Wendell Gilliam; James L. Robinson; Russell B. Brinsfield; Kenneth W. Staver; William Lucas; et al. (Environmental Management, 1997)

Studies of Mass-Movement Processes on Submarine Slopes - Lincoln Pratson; Homa Lee; Gary Parker; Marcelo Garcia; Bernard Coakley; David Mohrig; Jacques Locat; Ulisses Mello; Jeffrey Parsons; Sun-Uk Choi; Kenneth Isreal (Oceanography, 1996)

s 60th annual meeting The Potato Association of America - R. Kunkel; N. M. Holstad; R. E. Thornton; J. C. Bishop; Herman Timm; V. C. Shekhar; W. M. Iritani; Thornton Robert; Gary Hyde; Malamud Oscar; Robert B. O’Keefe; Mccown Brent; et al. (American Journal of Potato Research, 1976)